2018
DOI: 10.12998/wjcc.v6.i5.64
|View full text |Cite
|
Sign up to set email alerts
|

New insights ofHelicobacter pylorihost-pathogen interactions: The triangle of virulence factors, epigenetic modifications and non-coding RNAs

Abstract: Helicobacter pylori (H. pylori) is a model organism for understanding host-pathogen interactions and infection-mediated carcinogenesis. Gastric cancer and H. pylori colonization indicates the strong correlation. The progression and exacerbation of H. pylori infection are influenced by some factors of pathogen and host. Several virulence factors involved in the proper adherence and attenuation of immune defense to contribute the risk of emerging gastric cancer, therefore analysis of them is very important. H. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…Serum H19, LINC00152, and Lnc‐SGK1 may serve as potential biomarkers for the diagnosis of H. pylori GC (Yang et al, ; Yao et al, ). In H. pylori (+) GC serum, miR‐146, miR‐375, and Let‐7 were downregulated and miR‐19 and miR‐21 were upregulated for H. pylori clearance (Polakovicova et al, ; Vaziri, Tarashi, Fateh, & Siadat, ). miR‐124 was reported to have a protective role through the inhibition of DNA damage in the etiology of H. pylori ‐associated GC (Murray‐Stewart et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Serum H19, LINC00152, and Lnc‐SGK1 may serve as potential biomarkers for the diagnosis of H. pylori GC (Yang et al, ; Yao et al, ). In H. pylori (+) GC serum, miR‐146, miR‐375, and Let‐7 were downregulated and miR‐19 and miR‐21 were upregulated for H. pylori clearance (Polakovicova et al, ; Vaziri, Tarashi, Fateh, & Siadat, ). miR‐124 was reported to have a protective role through the inhibition of DNA damage in the etiology of H. pylori ‐associated GC (Murray‐Stewart et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the DNA can be methylated at cytosine or adenosine residues converting them into methyl-cytosine or methyl-adenosine to cause transcriptional repression [30]. Hypermethylation dominantly occurs at CpG islands, cytosine-guanine rich regions at promotor regions, disrupting TFs and RNA polymerase binding to DNA or recruiting other co-repressors.…”
Section: Epigenetic Control Of Gene Expressionmentioning
confidence: 99%
“…Moving away from the old definition of epigenetics as hereditable stable changes at chromatin and DNA without changing its sequence, modern opinion changed towards a highly dynamic and reversible mechanism of gene regulation also enabling short term adaptions to changing environments [30]. As consequence, regulation through ncRNAs are also included to the epigenetic regulatory repertoire that can be classified according to their length into short ncRNAs (<200 nucleotides), which include miRNAs or long ncRNAs (>200 nucleotides) [33].…”
Section: Epigenetic Control Of Gene Expressionmentioning
confidence: 99%
“…Studies have shown that intracellular pathogens can regulate cell signalling pathways and achieve immune escape by regulating the expression profiles of host lncRNAs, 11 such as Rickettsial , 12 Mycobacterium tuberculosis , 13 Helicobacter pylori 14 and Listeria monocytogenes . 15 C .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that intracellular pathogens can regulate cell signalling pathways and achieve immune escape by regulating the expression profiles of host lncRNAs, 11 such as Rickettsial, 12 Mycobacterium tuberculosis, 13 Helicobacter pylori 14 and Listeria monocytogenes. 15 C. trachomatis, as an intracellular pathogen, causes physiological changes in the host similar to those of the virus and changes the expression profile of the host mRNA, thus promoting its infection.…”
mentioning
confidence: 99%